2006
DOI: 10.1002/chem.200501178
|View full text |Cite
|
Sign up to set email alerts
|

Optical Processing with Photochromic Switches

Abstract: The absorbance, fluorescence, and refractive index of a photochromic material can be modulated under the influence of optical stimulations. The reversible modification of these macroscopic properties is a result of photoinduced transformations at the molecular level. These processes can be exploited to mediate the interplay of optical signals and offer the opportunity to design and implement photonic devices for optical processing based on molecular components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(82 citation statements)
references
References 43 publications
0
80
0
2
Order By: Relevance
“…The potential application of these components in optical and electronic memory devices has attracted considerable effort to this research area. [2] Of particular interest is the design of fluorescent molecular switches, as they can precisely control the fluorescence properties by simple chemical input, even down to the level of single molecules or ions under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential application of these components in optical and electronic memory devices has attracted considerable effort to this research area. [2] Of particular interest is the design of fluorescent molecular switches, as they can precisely control the fluorescence properties by simple chemical input, even down to the level of single molecules or ions under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Some time ago we found a seco-cyclo isomerism which is based on the reversible intramolecular [4π+4π]photocycloaddition of benzene rings to anthracene. [16] The utility of such a system depends strongly on clean switching processes in both directions.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] A number of molecular switches and logic gates based on SP derivatives are reported. [4][5][6][7][8][9][10] Meanwhile, assemblies of SP compounds and relevant photomodulation have also attracted attention. In the 1970's, Krongauz et al reported the formation of MC aggregates (referred to as ''quasicrystals'') upon UV irradiation of SP molecules in aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%